Development of immunogold test strips for chilli veinal mottle virus detection using monoclonal antibodies against the CP - Wang, Fang; Xu, Chuantao; Chen, Ying; Wang, Ke; An, Xueying; Zhou, Benguo (Frontiers in Microbiology, 2025)
Chilli veinal mottle virus (ChiVMV), a member of the Potyviridae family, a major threat to solanaceous crops, including tobacco and peppers, in China, where it causes systemic necrosis, leaf mottling, and significant yield losses. Early and accurate detection is essential for effective disease management, yet conventional assays such as RT-PCR and ELISA are constrained by laboratory requirements and skilled personnel. In this study, we developed a colloidal gold-based immunochromatographic strip (ICS) for the rapid, specific, and field-deployable detection of ChiVMV. The viral coat protein (CP) was heterologously expressed in Escherichia coli and used to generate eight hybridoma cell lines, from which two monoclonal antibodies, 22F4 (capture) and 45C4 (detector), were selected. The assembled ICS yielded clear visual results within 5–10 min, with a detection limit corresponding to a 1:1,000 dilution of infected leaf extracts, and exhibited no cross-reactivity with PVY, TVBMV, WYMV, TMV, or CMV. Field testing with 120 tobacco samples demonstrated 95.7% sensitivity and 98.0% specificity, consistent with RT-PCR, and the test strips maintained stability after 12 months of storage at room temperature. This study presents the first rapid ICS for ChiVMV, providing a sensitive, specific, and cost-effective diagnostic tool for on-site disease surveillance and early management in tobacco cultivation.